Hybrid Semantic Ontology Data (HSOD) Analysis Algorithm for Heterogeneous Tourism Information - Subhalakshmi, S; Rosy, C. Premila (International Journal of Computer Sciences and Engineering, 2025)
This technique is an ontology-based approach and a formal concept analysis (FCA) approach to integrating heterogeneous tourism information for online tour planning. Two ontologies, ontology for tourists and ontology for tourism information providers, are developed with respect to their own perspective. The ontology for tourists is developed from the tourism literature. The ontology for tourism information providers is developed by integrating heterogeneous online tourism information using a FCA approach. This HSOD Hybrid Semantic Ontology Data (HSOD) Analysis is then mapped using the FCA and Bayesian analysis to evaluate tourists' preferences against information published by tourism information providers. An example of planning a tour to Thanjvaur, Trichy is used to illustrate the proposed ontology approach. An analytic hierarchy process is used to rank the tourism attractions suggested by the ontology and FCA based approaches